THE ROLE OF THE CONSTITUTIONAL COURT IN MAINTAINING THE STABILITY OF THE CONSTITUTIONAL SYSTEM - Endro Suryono, Kelik (Hukum Responsif, 2025)
The Constitutional Court (MK) is pivotal in preserving the stability of Indonesia's constitutional framework by ensuring that laws and regulations align with the 1945 Constitution. The Constitutional Court, as a constitutional guardian institution, is responsible for evaluating laws, adjudicating power conflicts among state entities, dissolving political parties, and resolving electoral disputes. The role of the Constitutional Court is becoming increasingly vital in preserving the equilibrium of power among the administrative, legislative, and judicial branches, as well as in averting governmental overreach. Nonetheless, in its execution, the Constitutional Court has numerous problems, including political pressure, ambiguity in the enforcement of rulings, and discussions on the scope of its jurisdiction. Consequently, strategic measures are required to enhance decision-making consistency, reinforce the execution of the Constitutional Court's rulings, and preserve the autonomy of this institution from political interference. Furthermore, improving transparency in the decision-making process and fostering public engagement in comprehending the role of the Constitutional Court are essential for fortifying the rule of law and democracy in Indonesia.